Ludwig von Beethoven - Unknown:::Creator::::::::::::; Stieler, Joseph Karl, 1781-1858 (artist):::Contributor:::::::::::: (London; United Kingdom; William Macintosh, 24 Paternoster Row, 2021)
Image of Beethoven based on the portrait by Stieler